Pemahaman Konsep Siswa Menggunakan Model Pembelajaran Problem Based Learning (PBL) Berbantuan Aplikasi Geogebra - Putri, Sinta Maidatul; Susanto, Andi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This study was motivated by the low ability of concept understanding assisted by class VII SMP N 1 Padang Panjang. This is because the selected media-assisted learning model has not developed concept understanding skills. The solution is to use Problem Based Learning Model assisted by GeoGebra Application. This study aims to determine the concept understanding ability of students who learn using the Problem Based Learning Model assisted by Geogebra Application is higher than the concept understanding ability of students who learn using ordinary lessons. The type of research is quasy experiment with control group only design. The population is VII grade students of SMP N 1 Padang Panjang. The instrument used is a test of concept understanding ability assisted by data analyzed by t-test. The experimental class concept understanding ability test results were 79.33 assisted control class was 70.33. Hypothesis test Â with obtained tcount = 1,81 andÂ Â . It is concluded that the ability to understand concepts taught with Problem Based Learning Model assisted by GeoGebra Application is higher than the ability to understand the concepts of students with ordinary learning.Penelitian ini dilatarbelakangi rendahnya kemampuan pemahaman konsep berbantuan kelas VII SMP N 1 Padang Panjang. Hal ini dikarenakan model pembelajaran berbantuan media yang dipilih belum mengembangkan kemampuan pemahaman konsep. Adapun solusi dilakukan adalah menggunakan Model Problem Based Learning berbantuan Aplikasi GeoGebra. Penelitian ini bertujuan untuk mengetahui kemampuan pemahaman konsep siswa yang belajar menggunakan Model Pembelajaran Problem Based Learning berbantuan Aplikasi Geogebra lebih tinggi dibandingkan kemampuan pemahaman konsep siswa yang belajar menggunakan pelajaran biasa. Jenis penelitian adalah quasy eksperiment dengan control group only design. Populasimya adalah siswa kelas VII SMP N 1 Padang Panjang. Instrumen yang digunakan adalah tes kemampuan pemahaman konsep berbantuan data dianalisis dengan uji-t. Hasil tes kemampuan pemahaman konsep kelas eksperimen adalah 79.33 berbantuan kelas kontrol adalah 70.33. Uji hipitesis dengan didapatkan . Disimpulkan bahwa kemampuan pemahaman konsep yang diajar dengan Model Pembelajaran Problem Based Learning berbantuan Aplikasi GeoGebra lebih tinggi dari pada kemampuan pemahaman konsep siswa dengan pembelajaran biasa.